Boron Trifluoride as an Efficient Catalyst for the Selective Synthesis of Tricyclic Monoperoxides from β,δ-Triketones and H2O2 - Terent’ev, Alexander O.; Yaremenko, Ivan A.; Vil’, Vera A.; Dembitsky, Valery M.; Nikishin, Gennady I. (Synthesis, 2013)
Boron trifluoride was found to serve as an efficient catalyst for the reaction of β,δ-triketones with H2O2 producing tricyclic monoperoxides in yields from 48–93%. BF3 acts simultaneously as a catalyst and co-solvent. The synthesis can be scaled up to tens of grams. The resulting peroxides can be easily isolated from the reaction mixture by column chromatography.
Keywords: boron trifluoride; catalyst; peroxides; triketones; hydrogen peroxide